Antipsychotics reduces mortality in patients with neuropsychiatric systemic lupus erythematosus: a retrospective study of psychiatric consultation cases - Geng, Wenqi; Zhang, Shangzhu; Cao, Jinya; Zhu, Boheng; Duan, Yanping; Hong, Xia; Wei, Jing (Frontiers in psychiatry, 2023)
This study aimed to identify the presence of psychiatric comorbidities as well as investigate the relationship between psychiatric interventions for mental symptoms and mortality in patients with systemic lupus erythematosus (SLE).ObjectiveThis study aimed to identify the presence of psychiatric comorbidities as well as investigate the relationship between psychiatric interventions for mental symptoms and mortality in patients with systemic lupus erythematosus (SLE).We retrospectively evaluated the records of 160 inpatients with SLE who required psychiatric consultation for further therapeutic intervention from 2013 to 2020 in a tertiary general hospital. We collected clinical data, including diagnoses, medications, and mortality rate. We compared clinical characteristics among the diagnosis groups and correlations between variables.MethodWe retrospectively evaluated the records of 160 inpatients with SLE who required psychiatric consultation for further therapeutic intervention from 2013 to 2020 in a tertiary general hospital. We collected clinical data, including diagnoses, medications, and mortality rate. We compared clinical characteristics among the diagnosis groups and correlations between variables.A total of 138 (86.3%) patients met the diagnostic criteria for at least one mental disorder, with the most common being delirium (54.4%). The average Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI-2K) score significantly differed among the diagnosis groups (p = 0.003). The mortality rate among patients with delirium was significantly higher than that in the other patient groups (x2 = 12.967, p = 0.024). SLEDAI-2K score was not significantly correlated with mortality (r = 0.123, p = 0.087). Antipsychotics use was associated with mortality (odds ratio 0.053, p = 0.021).ResultsA total of 138 (86.3%) patients met the diagnostic criteria for at least one mental disorder, with the most common being delirium (54.4%). The average Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI-2K) score significantly differed among the diagnosis groups (p = 0.003). The mortality rate among patients with delirium was significantly higher than that in the other patient groups (x2 = 12.967, p = 0.024). SLEDAI-2K score was not significantly correlated with mortality (r = 0.123, p = 0.087). Antipsychotics use was associated with mortality (odds ratio 0.053, p = 0.021).Antipsychotic use may decrease death risk for patients with NPSLE. Early psychiatric consultation is necessary for patients with SLE who have developed or have suspected psychiatric symptoms in order to establish a comprehensive intervention plan.ConclusionAntipsychotic use may decrease death risk for patients with NPSLE. Early psychiatric consultation is necessary for patients with SLE who have developed or have suspected psychiatric symptoms in order to establish a comprehensive intervention plan.